Learning in student‐run clinics: a systematic review. Issue 3 (March 2015) - Schutte, Tim; Tichelaar, Jelle; Dekker, Ramon S; van Agtmael, Michiel A; de Vries, Theo P G M; Richir, Milan C
<x xml:space="preserve">Abstract</x> Discuss ideas arising from the article at www.mededuc.com discuss.